Reflections on Brexit and Migration: Literature Review - Guerrero Molina, María Isabel; Salazar Acevedo, Juan Felipe; Taborda Giraldo, Julián (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The uncertainty generated by the separation of the United Kingdom from the European Union is a historic and unprecedented event, leading to an atmosphere of discord within and outside the economic block, especially for migrants, due to the consequences that Brexit has unleashed. The literature review was based on a scientific mapping of the influence of European migrants, approached from the Brexit and the consequences on migration trends and policies. The Scopus database was used in the period 2015-2021, using bibliometric tools and RStudio the topic was reviewed based on the tree metaphor; it concludes with 3 study themes: social and cultural perspective of migrants; economic and labor impact associated with Brexit and; politics, debates and voting on consequences of Brexit, which allow determining a trend on the evolution and consequences of the separation of the United Kingdom from the European Union.